Reflections on the in-prison recruitment and participation of men with a history of injecting drug use, in a longitudinal cohort study in Australia. Issue 4 (December 2022) - Walker, Shelley; Curtis, Michael; Woods, Emma; Pierce, Lyn; Kirwan, Amy; Stewart, Ashleigh C; Cossar, Reece; Winter, Rebecca; Dietze, Paul; Kinner, Stuart A; Ogloff, James RP; Butler, Tony; et al.
Studies aimed at improving the health and well-being needs of people in prison are increasing in number. The ethical and logistical challenges of conducting this research, however, pose challenges for researchers which can limit its scope. Emerging literature provides insights into these challenges, but little is focused on the Australian perspective, and most are based on the experiences of recruiting and collecting data for ethnographic and qualitative research. Literature describing the challenges of conducting quantitative prospective studies in prisons is limited. Furthermore, despite the fact that people who inject drugs are overrepresented amongst prison populations, and experience higher levels of socioeconomic disadvantage and poorer health than the general prison population, we are unaware of literature describing the particular sensitivities associated with their recruitment and participation in research in prisons. We intend to address these gaps by drawing on our experience and reflecting on learnings that emerged from longitudinal research we conducted with 400 incarcerated males with recent histories of injecting drug use, in Victoria, Australia. Our aim is to provide guidance and lessons for future research.